Design and hardware-in-the-loop test of a coupled drive system for electric tractor. (April 2022) - Xie, Bin; Wang, Shuai; Wu, Xiuheng; Wen, Changkai; Zhang, Shengli; Zhao, Xueyan
Abstract : To solve problems of insufficient load capacity and poor operational efficiency, a new drive system for electric tractors was proposed. It consisted of dual electric motors and a coupled transmission system. The mechanical structure of the drive system of the electric tractor was designed and a prototype was manufactured. The switching rules of the drive system under typical working conditions (ploughing and rotary tillage) were established. Mathematical models of the drive system and the electric tractor were built for designing switching rules rapidly in a personal computer. Then it can be downloaded to the controller for implementing the hardware-in-the-loop (HIL) experiments. Actual data from previous field test of ploughing and rotary tillage were obtained and used as the loads in the HIL experiments. The power performance and operational efficiency of the drive system under these loads were analysed. It showed that the drive system could operate normally in typical working conditions. In terms of efficiency, simulation results showed that the drive system could improve during ploughing and rotary tillage by 9.92% and 12.36% respectively. Results from the HIL test showed that the drive system could improve efficiency of ploughing and rotary tillage by 11.35% and 11.70%, respectively. This research results concluded that the drive system could provide the loading capacity of large loads in typical working conditions, and the operational efficiency is significantly improved. Highlights: A new drive system with dual electric motors was designed for the electric tractor. The smooth switching rules between multiple operation modes were researched. The HIL test platform with the instrument system and the physical system was built. The power performance and efficiency of the drive system were verified by the HIL test.